The Implementation of Peer Interaction to Enhance Students' English Speaking Skills - Umi Qoni'ah; Umar Alfaruq A. Hasyim; Mai Zuniati; Irhamudin Irhamudin (Jurnal Ilmiah Iqra', 2025)
This Classroom Action Research investigated the effectiveness of the peer interaction strategy in enhancing tenth-grade students’ speaking skills at SMA Islam Sabilunnajah. Conducted over two cycles with seven meetings, including six treatment sessions, the study followed the stages of planning, acting, observing, and reflecting. The results demonstrated significant improvement, with the average score rising from 67.4 in cycle 1 (52.4% meeting the minimum competency criterion) to 75.8 in cycle 2 (80% meeting the criterion). The findings indicate that peer interaction fosters a more engaging and supportive classroom environment, making it an effective approach for improving speaking skills. This study provides valuable insights into systematically implementing peer interaction in EFL classrooms, offering educators innovative, socially interactive learning strategies to enhance students’ confidence and proficiency in English communication.